2023
DOI: 10.1186/s12871-023-02143-8
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative effect of sufentanil preemptive analgesia combined with psychological intervention on breast cancer patients

Abstract: Objectives To explore the postoperative effects of sufentanil preemptive analgesia combined with psychological intervention on breast cancer patients undergoing radical surgery. Methods 112 female breast cancer patients aged 18–80 years old who underwent radical surgery by the same surgeon were randomly divided into 4 groups, and there were 28 patients in each group. Patients in group A were given 10 µg sufentanil preemptive analgesia combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Sufentanil finds its applicability in diverse pain management scenarios, serving as an effective choice for postoperative analgesia, particularly following surgical and gynecological procedures, and is indispensable in the fields of anesthesia and pain management [8]. Its principal mechanism of action involves targeting opioid µ receptors, making it frequently used as an opioid analgesic [9]. It has been reported that the analgesic potency of Sufentanil surpasses that of fentanyl by a magnitude of 5-10 times [9] and that Sufentanil, as a fatsoluble substance, has high binding rates to plasma protein [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sufentanil finds its applicability in diverse pain management scenarios, serving as an effective choice for postoperative analgesia, particularly following surgical and gynecological procedures, and is indispensable in the fields of anesthesia and pain management [8]. Its principal mechanism of action involves targeting opioid µ receptors, making it frequently used as an opioid analgesic [9]. It has been reported that the analgesic potency of Sufentanil surpasses that of fentanyl by a magnitude of 5-10 times [9] and that Sufentanil, as a fatsoluble substance, has high binding rates to plasma protein [9].…”
Section: Introductionmentioning
confidence: 99%
“…Its principal mechanism of action involves targeting opioid µ receptors, making it frequently used as an opioid analgesic [9]. It has been reported that the analgesic potency of Sufentanil surpasses that of fentanyl by a magnitude of 5-10 times [9] and that Sufentanil, as a fatsoluble substance, has high binding rates to plasma protein [9]. In addition, research has shown that Sufentanil preconditioning exerts a protective effect on brain-related diseases [10], as well as antitumor effects [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation